Respuesta:
2
Explicación paso a paso:
5x - 11 = 2Ax - 3A + Bx + 2B
5x - 11 = x(2A + B) - 3A + 2B
2A + B = 5
B = 5 - 2A
-3A + 2B = -11
-3A + 2(5 - 2A) = -11
-3A + 10 - 4A = -11
-7A = -11 - 10
-7A = -21
A = -21/-7
A = 3
B = 5 - 2(3)
B = 5 - 6
B = -1
A + B
3 + (-1)
3 - 1
-7A = 1
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
2
Explicación paso a paso:
5x - 11 = 2Ax - 3A + Bx + 2B
5x - 11 = x(2A + B) - 3A + 2B
2A + B = 5
B = 5 - 2A
-3A + 2B = -11
-3A + 2(5 - 2A) = -11
-3A + 10 - 4A = -11
-7A = -11 - 10
-7A = -21
A = -21/-7
A = 3
B = 5 - 2A
B = 5 - 2(3)
B = 5 - 6
B = -1
A + B
3 + (-1)
3 - 1
2
-7A = 1